2023
DOI: 10.1152/ajpheart.00430.2022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling incomplete penetrance in long QT syndrome type 3 through ion channel heterogeneity: an in silico population study

Abstract: Many cardiac diseases are characterized by an increased late sodium current, including heart failure, hypertrophic cardiomyopathy, and inherited long QT syndrome type 3 (LQT3). The late sodium current in LQT3 is caused by a gain-of-function mutation in the voltage-gated sodium channel Nav1.5. Despite a well-defined genetic cause of LQT3, treatment remains inconsistent due to incomplete penetrance of the mutation and variability of anti-arrhythmic efficacy. Here, we investigate the relationship between LQT3-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…They further show that this relationship is not demonstrated in models of reduced repolarization reserve (i.e., heart failure rabbit and pig cardiomyocytes). Lastly, a study by Miller et al (Miller et al, 2023) found that susceptibility to arrhythmia is decreased with a higher I Kr -to-I Na ratio in a LQT3 model. Therefore, in a model of increased I Kr , and high RRC size, increases in I NaL could be important in preventing pathophysiology.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…They further show that this relationship is not demonstrated in models of reduced repolarization reserve (i.e., heart failure rabbit and pig cardiomyocytes). Lastly, a study by Miller et al (Miller et al, 2023) found that susceptibility to arrhythmia is decreased with a higher I Kr -to-I Na ratio in a LQT3 model. Therefore, in a model of increased I Kr , and high RRC size, increases in I NaL could be important in preventing pathophysiology.…”
Section: Discussionmentioning
confidence: 94%
“…There have been studies that provide a more global view on repolarization reserve (Sarkar and Sobie, 2011; Britton et al, 2017; Miller et al, 2023). Sarkar and Sobie (2011) used multivariable regression to quantify repolarization reserve after 75% I Kr block; Britton et al (2017) used a population of models approach to study repolarization abnormalities upon multichannel ionic block of I Kr , I Ks , I K1 , and I CaL ; and Miller et al (2023) published a population of models study that provided insight to ion-channel conductance correlations that play a role in LQT3 susceptibility. All these studies provide valuable insights to arrhythmia resistance in the case of decreased repolarization reserve by using ion-channel block or disease mutation models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations